(untitled) (MAUSAM, 2016)
Natural extreme weather events have been causing excessive damage to life and property across the globe since time immemorial. Space based techniques and instruments have been improvised and utilised over the years to generate and collect earth observations data. Although a significant amount of research has led to meaningful forecasts of extreme weather events leading to minimising of the loss of life and property, the analytical approaches in this field need to be further studied and explored. Also, since every instance of earth observation is significant in multiple time domains (current as well as past which is required for climatology studies), it needs to be archived and disseminated in an organised and holistic manner. For long time preservation, modern infrastructure and underlying cutting edge technologies need to be adapted. With missions like GISAT, where the volume of data handled per day will be around 200 Mega bytes per second, multi level strategic approach for archival and high speed bandwidth for near real time data dissemination on public networks should be complemented with data broadcast to strategic users, using satellite communications. This paper describes the current infrastructure established for archival and dissemination and archival of ISRO’s Met-Ocean data observations and the future road map in the area of instantaneous data and weather alerts dissemination through an Indian broadcasting system (IMETCAST). This is to ensure timely delivery of satellite data to end users to facilitate near real time analysis of weather events.